Linear algebra and its tools for data mining - Simovici, Dan A. (World Scientific, 2012)
Linear Algebra and Its Tools for Data Mining presents fundamental concepts and methods of linear algebra applied to data mining and machine learning. The book provides a solid mathematical foundation for data processing, principal component analysis, dimensionality reduction, and optimization, highlighting the essential role of linear algebra in modern data science techniques.